Strategi dan Tantangan dalam Menuju Pasar Global pada UMKM "Miz Titin" - Rizky, Muhammad; Arista, Sintha Wahyu; Dewi, Linda Intania; Purnawan, Steven Owen; Sriyono, Sriyono (Jurnal E-Bis, 2024)
This research aims to explore effective methods for expanding market reach and identify the main obstacles that may be encountered. The methodology used includes case studies and in-depth interviews with MSME owners as well as analysis of relevant literature. The research results show that the main strategies implemented include product quality evaluation, use of technology, business development, and relationships with customers in global market orientation and innovation. The challenges faced include competitors, human resources, services, markets, raw materials and brand image in the global market network and efficiency. In conclusion, researchers hope that in the future the development of MSMEs in the global market sector will continue to be carried out and supported by all levels of society where the government plays an important role regarding the development of MSMEs, such as regulations and training guidance for MSMEs so they can compete in the global market.